2002
DOI: 10.1055/s-2002-20525
|View full text |Cite
|
Sign up to set email alerts
|

Central 5-HT3 Receptor Stimulation by m-CPBG Increases Blood Glucose in Rats

Abstract: The aim of the present study was to investigate the role of central 5-HT3 receptors on the control of blood glucose in stressed and non-stressed rats in both fasted and fed states. Adult Wistar male rats had each their third ventricle cannulated 7 days before the experiments. Injections of m-CPBG, a selective 5-HT3 receptor agonist, induced a significant increase in blood glucose in non-stressed rats in both fasted and in fed states. The same procedure was unable to modify stress-induced hyperglycemia. The hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[47]. It has been shown that administration of ondansetron, a 5-HT 3 receptor antagonist, reduced elevated level of blood glucose in stressed rats stimulated by meta-chlorophenylbiguanide (m-CPBG) [48]. Another report indicated that tropisetron is able to enhance the insulin release in the beta-cell line (INS-1) [49], especially in presence of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…[47]. It has been shown that administration of ondansetron, a 5-HT 3 receptor antagonist, reduced elevated level of blood glucose in stressed rats stimulated by meta-chlorophenylbiguanide (m-CPBG) [48]. Another report indicated that tropisetron is able to enhance the insulin release in the beta-cell line (INS-1) [49], especially in presence of serotonin.…”
Section: Discussionmentioning
confidence: 99%
“…OH-DPAT, a selective 5-HT 1A agonist, increases blood glucose levels when administered centrally [33]. Carvalho et al [34] have shown that activation of central 5-HT 3 receptors by the selective agonist m -chlorophenylbiguanide produces hyperglycemia in both fasted and fed rats and that this is blocked by ondansetron. …”
Section: Discussionmentioning
confidence: 99%
“…The lack of this higher endogenous CRH−related Quipazine is a serotonergic agonist that stimulates 5−HT 1 , 5−HT 2 and 5−HT 3 receptors. We have previously demonstrated that cen− tral pharmacological activation of 5−HT 3 receptors by the selec− tive agonist m−CPBG increases plasma glucose levels [9]. In the present paper, we have shown that quipazine−induced hypergly− cemia is, at least in part, due to the activation of central 5−HT 3 re− ceptors since pretreatment with two different selective 5−HT 3 antagonists, LY−278,584 and ondansetron, was able to reduce quipazine enhancement of plasma glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the central administration of selective 5− HT 2A and 5−HT 2C receptor agonists enhances blood glucose by a mechanism that seems to be dependent on peripheral adrenaline release [7,8]. We have recently shown that pharmacological acti− vation of central 5−HT 3 receptors by the selective agonist m− CPBG provokes a significant increase in blood glucose [9].…”
Section: Introductionmentioning
confidence: 98%